SOCIAL INEQUALITY IN “KECHA VA KUNDUZ” AND ITS TRANSFORMATION IN CONTEMPORARY UZBEK SOCIETY (TAMADDUN NURI JURNALI, 2025)
This article explores the theme of social inequality in Abdulla Qodiriy’s novel Kecha va Kunduz and examines its transformation in contemporary Uzbek society. By comparing the literary depiction of class, gender, and educational disparities with current sociological data, the study reveals the persistence of structural and symbolic inequality. Employing an interdisciplinary approach that combines literary analysis with the theoretical frameworks of Pierre Bourdieu and gender studies, the paper argues that the issues highlighted in the novel remain relevant today.